2021
DOI: 10.1016/j.aucc.2020.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Protection procedures and preventions against the spread of coronavirus disease 2019 in healthcare settings for nursing personnel: Lessons from Taiwan

Abstract: Background Since the coronavirus disease 2019 (Covid-19) was first discovered, at the time of writing this article, the number of people infected globally has exceeded one million. Its high transmission rate has resulted in nosocomial infections in health care facilities all over the world. Nursing personnel account for nearly 50% of the global health workforce and are the primary provider of direct care in hospitals and long-term care facilities. Nurses stand on the frontline against the spread o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 42 publications
2
17
0
6
Order By: Relevance
“…In the present study, only one third of the population from each group was of physicians, and none of them got sick. Additionally, it was observed that the highest number of COVID-19 positive individuals were female nurses from the control group; this is in agreement with other studies that describe a high incidence of SARS-CoV-2 infection in nurses, since they spend more time with patients than physicians do [30]. Other studies about the risk of infection considered populations with similar gender proportions and concluded that the probability of getting infected is equal for both sexes [31,32].…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, only one third of the population from each group was of physicians, and none of them got sick. Additionally, it was observed that the highest number of COVID-19 positive individuals were female nurses from the control group; this is in agreement with other studies that describe a high incidence of SARS-CoV-2 infection in nurses, since they spend more time with patients than physicians do [30]. Other studies about the risk of infection considered populations with similar gender proportions and concluded that the probability of getting infected is equal for both sexes [31,32].…”
Section: Discussionsupporting
confidence: 89%
“…This was in line with the experience of hard-hit countries during the outbreak’s first wave, such as Spain, Italy and the US The US reported that 18% of cases occurred in healthcare workers early in the pandemic [ 23 ]. Additionally, early on, between 28 February 2020, and 23 April 2020, Spain reported that 20.4% of its cases had occurred in healthcare workers, and during the same time period Italy reported a 10.7% rate of infection among healthcare workers [ 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…These CoVs can cause less-pathogenic endemic diseases in infected hosts. However, in 2003, a severe pandemic occurred resulting in more than 8422 cases and about 916 related deaths caused by another strain of CoV, namely severe acute respiratory syndrome (SARS)-CoV 3 - 6 . In 2012, another CoV strain, namely the Middle East respiratory syndrome (MERS)-CoV, that infected humans, bats, and camels also caused more than 4494 cases and 858 deaths 7 .…”
Section: Introductionmentioning
confidence: 99%